2012
DOI: 10.1002/jor.22181
|View full text |Cite
|
Sign up to set email alerts
|

Current insights on the regenerative potential of the periosteum: Molecular, cellular, and endogenous engineering approaches

Abstract: While century old clinical reports document the periosteum's remarkable regenerative capacity, only in the past decade have scientists undertaken mechanistic investigations of periosteum's regenerative potential. Here we outline three presentations from a 2012 Orthopaedic Research Society Workshop which reviewed the current state of the art in molecular, cellular and tissue scale approaches to elucidate the mechanisms underlying the periosteum's regenerative potential and translational therapies as well as eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
192
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(200 citation statements)
references
References 100 publications
2
192
0
6
Order By: Relevance
“…These cells then initiate a cascade of growth factors and inflammatory cytokine and chemokine production that facilitate the recruitment of inflammatory immune cells (granulocytes and inflammatory monocyte/ macrophages) that combat infection and phagocytose debris and dead cell remnants. 25 During this inflammatory event, expansion/recruitment of mesenchymal stem/progenitor/precursor cells (be they from local or more distant locations 26 ) occurs and this is followed by replacement of the hematoma with a vascularized fibrous connective tissue, known as granulation tissue. 25 Macrophages are present during the inflammatory phase of fracture healing in both humans 27 and animals.…”
Section: Macrophage Contributions To Inflammation During Fracture Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…These cells then initiate a cascade of growth factors and inflammatory cytokine and chemokine production that facilitate the recruitment of inflammatory immune cells (granulocytes and inflammatory monocyte/ macrophages) that combat infection and phagocytose debris and dead cell remnants. 25 During this inflammatory event, expansion/recruitment of mesenchymal stem/progenitor/precursor cells (be they from local or more distant locations 26 ) occurs and this is followed by replacement of the hematoma with a vascularized fibrous connective tissue, known as granulation tissue. 25 Macrophages are present during the inflammatory phase of fracture healing in both humans 27 and animals.…”
Section: Macrophage Contributions To Inflammation During Fracture Repairmentioning
confidence: 99%
“…At this point, healing mechanisms diverge either toward direct bone deposition by intramembranous ossification (rigidly stabilized fractures) or toward periosteal callus formation via endochondral ossification (nonrigid fixation). In both cases, vital events are mesenchymal stem/progenitor/precursor cell recruitment/expansion (from distant or local pools 26 ) and subsequent induction of osteoblastogenesis or chondrogenesis, respectively. Data from animal models support the fact that macrophages are present within repair-associated tissues during this early anabolic phase with potentially sustained presence of robust numbers of macrophages during rigidly stabilized fixation compared with nonrigid repair scenarios.…”
Section: Macrophage Contributions To Early Anabolism During Fracture mentioning
confidence: 99%
“…This line of reasoning was bolstered by a careful histological examination of vasculature following fracture that nicely demonstrated the periosteal callus alone has extensive new vessel formation (69). Additionally, a body of experimental work has shown that the presence or absence of the periosteum significantly affects the healing response (70). Finally, recent work has demonstrated that invading blood vessels in the periosteal fracture callus are intimately associated with osteoblast precursors (71).…”
Section: Blood Flow During Fracturementioning
confidence: 99%
“…The early inflammatory phase of fracture healing, which is characterised by a complex interaction between immune cells, resident tissue cells and pro-and antiinflammatory cytokines and chemokines, is thought to initiate the repair cascade by attracting mesenchymal progenitor cells locally, including from the periosteum (Colnot et al, 2012) and the bone marrow (Taguchi et al, 2005 ). There is evidence suggesting that circulating MSC are physiologically recruited to the fracture site and contribute to osteogenesis (Kumagai et al, 2008), implying that increasing their numbers in the blood circulation by intravenous administration may support fracture repair.…”
Section: Introductionmentioning
confidence: 99%